Development of ecological and economic measures for creating of the sustainable land use - Hetmanchyk, I.; Kolhanova, I. (Land Management, Cadastre and Land Monitoring, 2017)
The article deals with ecological and economic measures for creating of the sustainable land use, it’s current state and problems as well as areas of improvement. These measures directed to ensure balanced of needs of the population and economic sectors by land resources, rational use and protection of lands, preservation of landscape and biological diversity, creation of environmentally safe living conditions of the population and economic activity and protection of lands from depletion, degradation and pollution. Key words: sustainable land use, lands of nature conservation and natural reserve purpose, ecological network, agrolandscape.